2019
DOI: 10.1186/s12936-019-2858-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic dose determination and efficacy of chlorfenapyr and clothianidin insecticides against Anopheles malaria vector populations of western Kenya

Abstract: Background Malaria vector control is dependent on chemical insecticides applied to walls by indoor residual spraying or on long-lasting insecticidal nets. The emergence and spread of insecticide resistance in major malaria vectors may compromise malaria control and elimination efforts. The aim of this study was to estimate a diagnostic dose for chlorfenapyr (class: pyrrole) and clothianidin (class: neonicotinoid) and assess the baseline susceptibility of three major Anopheles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 28 publications
8
49
1
Order By: Relevance
“…Despite these difficulties, the susceptibility of wild Anopheles populations from several African countries has been successfully evaluated using the recommended diagnostic doses of clothianidin [18,22,35,37 arabiensis [18,22,35,37]. Resistance to clothianidin was not detected among populations from 16 countries where 100% mortality was reached on average 72 h following exposure in all populations tested either with WHO tube tests [18,37] or with CDC bottle assays [22,35]. Our study confirms that susceptible populations of [18].…”
Section: -Oxydases Play a Central Role In Clothianidin Resistance Insupporting
confidence: 68%
See 4 more Smart Citations
“…Despite these difficulties, the susceptibility of wild Anopheles populations from several African countries has been successfully evaluated using the recommended diagnostic doses of clothianidin [18,22,35,37 arabiensis [18,22,35,37]. Resistance to clothianidin was not detected among populations from 16 countries where 100% mortality was reached on average 72 h following exposure in all populations tested either with WHO tube tests [18,37] or with CDC bottle assays [22,35]. Our study confirms that susceptible populations of [18].…”
Section: -Oxydases Play a Central Role In Clothianidin Resistance Insupporting
confidence: 68%
“…We tested the susceptibility of adult mosquitoes against a diagnostic dose of clothianidin using CDC bottle assays according to published guidelines [34]. A recent study showed that 150µg/ml clothianidin was a suitable diagnostic dose-the lowest concentration of active ingredient that kills 100% of individuals of a susceptible laboratory strain within 24 h of insecticide exposure [35]. To assess the intensity of resistance, we also determined the mortality rates of wild mosquitoes exposed to 5X and 10X the diagnostic dose.…”
Section: Cdc Bottle Testsmentioning
confidence: 99%
See 3 more Smart Citations